Does local lavage influence functional recovery during lumber discectomy of disc herniation?: One year's systematic follow-up of 410 patients. Issue 42 (October 2016) - Zhu, Ru-Sen; Ren, Yi-Ming; Yuan, Jian-Jun; Cui, Zi-Jian; Wan, Jun; Fan, Bao-You; Lin, Wei; Zhou, Xian-Hu; Zhang, Xue-Li
Abstract : Abstract: Lumbar disc herniation (LDH) is a common disease and lumbar discectomy is the most common surgical procedure carried out for patients with low back pain and leg symptoms. Although most researchers are focusing on the surgical techniques during operation, the aim of this study is to evaluate the effect of local intervertebral lavage during microdiscectomy. In this retrospective study, 410 patients were operated on by microdiscectomy for LDH during 2011 to 2014. Retrospectively, 213 of them (group A) accepted local intervertebral irrigation with saline water before wound closure and 197 patients (group B) only had their operative field irrigated with saline water. Systematic records of visual analog scores (VAS), Oswestry disability Index (ODI) questionnaire scale scores, use of analgesia, and hospital length of stay were done after hospitalization. The majority (80.49%) of the cases were diagnosed with lumber herniation at the levels of L4/5 and L5/S1. Fifty-one patients had herniations at 2 levels. There were significant decreases of VAS scores and ODI in both groups between preoperation and postoperation of different time points. VAS scores decreased more in group A than group B at early stage of postoperation follow-up. However, there were no statistically significant differences between 2 groups in using analgesia, VAS and ODI up to 1 month of follow-up. Microdiscectomy for LDH offers a marked improvement in back and radicular pain. Local irrigation of herniated lumber disc area could relief dick herniation-derived low back pain and leg radicular pain at early stage of post-operation. However, the pain relief of this intervention was not noticeable for a long period.